2016
DOI: 10.1007/s10544-016-0082-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel design for passive misscromixers based on topology optimization method

Abstract: In this paper, a series of novel passive micromixers, called topological micromixers with reversed flow (TMRFX), are proposed. The reversed flow in the microchannels can enhance chaotic advection and produce better mixing performance. Therefore the maximum of reversed flow is chosen as the objective function of the topology optimization problem. Because the square-wave unit is easier to fabricate and have better mixing performance than many other serpentine micromixers, square-wave structure becomes the origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…Oh et al [100] used the Navier-Stokes and a convection-diffusion equation to model and optimise the osmotic permeate flux over a membrane wall. Chen and Li [101] optimised micromixers under the assumption that reverse flow structures [8] inserted in a microchannel increases the mixing. Hyun et al [102] designed repeating units for sorting particles using principles in deterministic lateral displacement.…”
Section: Species Transportmentioning
confidence: 99%
“…Oh et al [100] used the Navier-Stokes and a convection-diffusion equation to model and optimise the osmotic permeate flux over a membrane wall. Chen and Li [101] optimised micromixers under the assumption that reverse flow structures [8] inserted in a microchannel increases the mixing. Hyun et al [102] designed repeating units for sorting particles using principles in deterministic lateral displacement.…”
Section: Species Transportmentioning
confidence: 99%
“…The optimal parameters (a 1 :a 2 :b = 5:6:4) for the ellipse were investigated with a high mixing efficiency of >80%, which was better than that of the T-channel mixer ( Figure 15 c). Recently, several convergence–divergence based micromixers, which were transformed from the typical two-dimensional serpentine channel and based on topology optimization method, were reported by Chen and Li [ 105 ]. In these micromixers, convergence-divergence structures were set at the center of the channel with the obstacles at different height ( Figure 15 d), The results showed that the micromixer with the ratio of the height of the convergence-divergence structure to that of the channel of 0.75 had the best mixing efficiency of over 95% for a wide range of Re ( Re ≥ 5 or Re ≤ 0.5).…”
Section: Passive Micromixermentioning
confidence: 99%
“…Passive strategies, on the other hand, rely on the channel geometry-fluid interaction to induce transversal flows that stretch the interface between the fluids components to be mixed, and advection, mimicking macroscale turbulence [17][18][19]. Arrays of obstacles [28][29][30][31], ridge-groove systems [32][33][34], two-or three-dimensional turns [35,36], and curved channel sections [17,37,38] have been successfully used to exploit the already existent pressure differentials necessary to push the fluids of interest along the microfluidic device, in order to generate cross-sectional flows capable of stretching, folding, and splitting fluid elements conducive to efficient mixing. Aside from a proven ability to reach the necessary mixing quality, passive designs benefit from being accessible to a variety of fabrication methods including soft lithography [39,40], 3D printing [41], and molecular imprinting [42].…”
Section: Introductionmentioning
confidence: 99%